A partial revision of the Australian Eulimnadia Packard, 1874 (Branchiopoda: Spinicaudata: Limnadiidae) - Timms, Brian V (Zootaxa, 2016)
The worldwide genus Eulimnadia previously with only five species described from Australia, is known now to have at least 15 endemic species plus about 10 undescribed species detected by molecular means. Most have variable morphological features, though each has a distinctive resting egg morphology. Many occur in the known branchiopod hot spot of the Paroo/Bulloo catchments in western New South Wales and Queensland. Some are specific to gnammas (rock holes). Given the rarity of males, androdioecious reproduction is probable in most species. Keys are provided for all known Australian species.